Managing the health risks associated with agriculture: An overview of research by the International Livestock Research Institute - Lore, Tezira A.; Grace, Delia (International Livestock Research Institute, 2014)
Over 60 per cent of the newly identified infectious diseases that have affected people over the past few decades have been caused by pathogens originating from animals or animal products. In agricultural areas that use more water, people face increased risk of infectious diseases, especially through zoonotic diseases (diseases transmissible from animals to people) as well as water-borne and vector-borne diseases. The CGIAR research program on agriculture for nutrition and health (A4NH) carries out research to maximize the nutritional and health benefits of agricultural development. The program has four research themes: value chains, biofortification, control of agriculture-associated diseases, and integrated programs and policies. The International Livestock Research Institute (ILRI) leads the research theme on the prevention and control of agriculture-associated diseases. Key areas of focus of this theme are: ● food safety: participatory risk assessment in milk and meat value chains in informal markets as well as risk and economic assessment of aflatoxins ● neglected zoonoses: epidemiology, ecology and socio-economics of disease emergence in urban areas ● emerging infectious diseases: mapping the risk of vector-borne diseases; determining the drivers of disease emergence and transmission; and modelling of disease transmission to improve decision-making towards preventing and controlling diseases The research outputs will be used by value chain actors, policymakers, development program implementers and governments to improve animal-source food value chains and prevent and control infectious diseases. Ultimately, this will lead to improved nutrition and health, especially among women and children.